NiAl₂O₄ -Modified Glassy Carbon Electrode From Napa Soil For Pb²⁺ Ions Using Voltammetry - Zsa Zsa Fitria Alizar; Mawardi Mawardi; Alizar Ulianas; Syamsi Aini; Okta Suryani (Universitas Pendidikan Mandalika, 2026)
Lead (Pb²⁺) is a toxic heavy metal that poses serious risks to environmental and human health, creating a need for sensitive and reliable detection methods. This study aimed to develop a glassy carbon electrode (GCE) modified with NiAl₂O₄ derived from Napa soil for the electrochemical detection of Pb²⁺ ions using voltammetric techniques. The electrochemical performance of the modified electrode was evaluated by cyclic voltammetry in 4 mM K₃[Fe(CN)₆] containing 0,1 M KCl. The results showed that the NiAl₂O₄-modified GCE exhibited enhanced electrochemical activity compared with the bare GCE, as indicated by an increase in anodic peak current from 19.93 μA to 26.60 μA (33.5%) and cathodic peak current from 19.03 μA to 24.29 μA (27.6%), reflecting improved electron-transfer capability and a larger electroactive surface area. The modified electrode successfully detected Pb²⁺ ions, producing well-defined oxidation and reduction peaks at −0.32 V and −0.52 V, respectively. Among the supporting electrolytes investigated, 0,1 M KCl provided the highest current response, and increasing the KCl concentration from 0.05 M to 0,10 M further enhanced the electrochemical signal. In addition, the electrode demonstrated good stability during repeated measurements. These findings indicate that the NiAl₂O₄-modified GCE based on Napa soil is a promising, low-cost, and sensitive electrochemical sensor for Pb²⁺ detection with improved electrochemical performance.